Von Willebrand factor and ADAMTS13 impact on the outcome of Staphylococcus aureus sepsis. (22nd December 2019) - Peetermans, Marijke; Meyers, Severien; Liesenborghs, Laurens; Vanhoorelbeke, Karen; De Meyer, Simon F.; Vandenbriele, Christophe; Lox, Marleen; Hoylaerts, Marc F.; Martinod, Kimberly; Jacquemin, Marc; Vanassche, Thomas; Verhamme, Peter
Abstract: Background: Previous clinical evidence correlates levels of von Willebrand factor (VWF) and its cleaving protease ADAMTS13 with outcome in septic patients. No previous studies addressed if VWF and ADAMTS13 affected the outcome of Staphylococcus aureus sepsis. Objectives: We studied the role of VWF and ADAMTS13 in S. aureus sepsis both in patients and in mice. Methods: VWF levels and ADAMTS13 activity levels were measured in plasma samples from 89 S. aureus bacteremia patients by chemiluminescent assays and were correlated with clinical sepsis outcome parameters. In wild‐type mice and mice deficient in VWF and ADAMTS13, we investigated the outcome of S. aureus sepsis and quantified bacterial clearance and organ microthrombi. Results: In patients with S. aureus bloodstream infections, high VWF levels and low ADAMTS13 activity levels correlated with disease severity and with parameters of inflammation and disseminated intravascular coagulation. In septic mice, VWF deficiency attenuated mortality, whereas ADAMTS13 deficiency increased mortality. Bacterial clearance was enhanced in VWF‐deficient mice. The differences in mortality for the studied genotypes were associated with differential loads of organ microthrombi in both liver and kidneys. Conclusions: In conclusion, this study reports the consistent relation of VWF, ADAMTS13 and their ratio to disease severity in patients and mice with S. aureus sepsis. Targeting VWF multimers and/or the relative ADAMTS13 deficiency that occurs in sepsis should be explored as a potential new therapeutic target in S. aureus endovascular infections.